If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -6 = 17y + 98 Reorder the terms: -6 + 4y = 17y + 98 Reorder the terms: -6 + 4y = 98 + 17y Solving -6 + 4y = 98 + 17y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-17y' to each side of the equation. -6 + 4y + -17y = 98 + 17y + -17y Combine like terms: 4y + -17y = -13y -6 + -13y = 98 + 17y + -17y Combine like terms: 17y + -17y = 0 -6 + -13y = 98 + 0 -6 + -13y = 98 Add '6' to each side of the equation. -6 + 6 + -13y = 98 + 6 Combine like terms: -6 + 6 = 0 0 + -13y = 98 + 6 -13y = 98 + 6 Combine like terms: 98 + 6 = 104 -13y = 104 Divide each side by '-13'. y = -8 Simplifying y = -8
| 8a^2-22a-21=0 | | y^2+4y=2-3x | | 2x*3+3x*3=540 | | 2(1-3m)=8(-2m-1) | | 3x(13+12)=33 | | X-2(180)=170 | | -5(2x+4)=9x | | 21+x=-5 | | -2x^2-7x+42=0 | | 8i+16.2=1.8 | | 4x+5+2x-11=180 | | a^2x+11ax+28x=0 | | -7x+4(x-3)=-33 | | 17.5*4= | | X+5+y=180 | | -9=a(9-5t) | | X+5+3x+5+y+2y+15=360 | | 7t-4=10n+14 | | 3.8y+8x=6 | | -8x=-4(x-4) | | 2(2x-4)-x-3=-14 | | log(8x+6)=1 | | 6(3n+2)=9(5n+9)+2 | | X+5+3x+5+y+2y+15=180 | | x^2+4x+161=0 | | -2a-9=6x+15 | | -3x-45=-11x+51 | | f(x)=-12x+48 | | .3x-2.3=.1 | | 2(4y-3)=-10 | | -7w+2(w+4)=3 | | 8+x=-21 |